A semiautomated microfluidic platform for real-time investigation of nanoparticles' cellular uptake and cancer cells' tracking. (March 2017) - Carvalho, Mariana R; Maia, F Raquel; Silva-Correia, Joana; Costa, Bruno M; Reis, Rui L; Oliveira, Joaquim M
Aim: Develop a platform composed of labeled dendrimer nanoparticles (NPs) and a microfluidic device for real-time monitoring of cancer cells fate.Materials & methods: Carboxymethylchitosan/poly(amidoamine) dendrimer NPs were labeled with fluorescein-5(6)-isothiocyanate and characterized using different physicochemical techniques. After, HeLa, HCT-116 and U87MG were cultured in the presence of NPs, and cell viability and internalization efficiency in static (standard culture) and dynamic (microfluidic culture) conditions were investigated.Results: Cancer cells cultured with NPs in dynamic conditions were viable and presented higher internalization levels as compared with static 2D cultures.Conclusion: This work demonstrated that the proposed microfluidic-based platform allows real-time monitoring, which upon more studies, namely, the assessment of an anticancer drug release effect could be used for cancer theranostics.